Degradação do H2S contido em poluentes gasosos utilizando fotocatalisador revestido de TiO2 - Lied, Eduardo Borges (2018)
Atmospheric emissions have been one of the biggest problems to be faced by agroindustries located in the western region of Paraná. The volume of scientific research results confirming the efficacy of the use of Advanced Oxidative Processes has been shown to be significant, and technological and innovation complementation is of the utmost importance in order to enable the application of this knowledge. The objective of this work was to develop an ALTERNATIVE TECHNOLOGY FOR DEGRADATION OF H2S PRESENT IN GASEOUS POLLUTANTS USING PHOTOCATALYST COATED WITH TiO2. For this, a rectangular reactor was developed and three types of photocatalysts based on acrylic paint, Fotosan® and polyurethane - and two from pure TiO2 supported on fiber cement and glass fiber were tested to evaluate the photocatalytic degradation of hydrogen sulphide (H2S) in the gas phase. The surfaces formed by these coatings were structural and morphologically characterized by scanning electron microscopy with dispersive energy X-ray spectroscopy (SEM-EDS) and X-ray diffractometry (XRD). The flow rate and the inlet concentration of H2S were evaluated as operational performance parameters of the reactor. Through artificial radiation UV degradation efficiencies were obtained by up to 95% degradation at a flow rate of 2 L min-1 (residence time of 1 min and 55 s) and initial concentration of 31 ppm of H2S using acrylic paint. The Italian photosan® photocatalyst was able to oxidize up to 75% at a flow rate of 2 L min-1. Regarding the use of solar radiation, acrylic paint did not present photocatalytic activity, while Fotosan® paint maintained a 75% efficiency. In addition, the H2S degradation kinetics were modeled according to the Langmuir-Hinshelwood (L-H), first order and second order models. For the acrylic paint the best fit corresponded to the second order model (k = 2.2x10-1 min -1 and R2 = 0.98), and for Fotosan® paint the first order model adequately represented the experimental data (k = 8.6x10-1 min-1 and R2 = 0.99). The results suggest that the flow has a more important influence on photocatalytic degradation than the feed concentration. Based on the analysis of FTIR-ATR, it is assumed that H2S was oxidized to SO42-, a condition that led to the deactivation of the photocatalyst after 190 min and 290 min of semi-continuous use for acrylic and Fotosan® paints, respectively. The study of the aging of the translucent materials (acrylic, glass and polycarbonate) revealed that glass is the material that has the greatest ability to maintain its optical properties (UV-Vis transmittance). Fluid dynamics simulation using the software Comsol Multiphysics 5.0 allowed to establish the speed profiles and calculate the residence times (RT) for each flow tested. The simulation concluded that the simulated RT values represent on average 26% the value of the theoretical RT for the studied flow range (2 to 14 L min-1). The notions of the fluid dynamics simulation were used to optimize the geometry of the final proposal of the alternative technology.